Budidaya Paper ningrum L. Dalam Rangka Meningkatkan Ekonomi Masyarakat Gambut di Kabupaten Tanjung Jabung Timur, Provinsi Jambi - Yudhi Achnopha (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
The distribution of peat land in Jambi Province is an opportunity for the peat community to be able to take advantage of it by planting plants that have a high selling value. This community service activity aims to improve the economy of the peat community through the transfer of knowledge in the form of proper seeding techniques and planting pepper on peat land planted on jelutung as stem stands. This community service activity uses an approach method to participants who are farmers or a combination of farmer groups who own land. This activity began with lectures and presentations on peatland issues and how to manage them, pepper seeding techniques, and planting and maintenance techniques in the field. The results of this community service activity have a positive impact on the life of the peat community in terms of the economy, where apart from farmers selling seeds at a price of Rp. 10,000, -/polybag, also farmers get big profits, reaching Rp. 3.800.000,-/plant/kg dry weight. The results of the activity also made a positive contribution where participants who had already received knowledge transfers could pass on their knowledge to other farmers in Mendahara District, Tanjung Jabung Timur Regency, Jambi Province.